Application of selected teak clone and organic fertilizer to accelerate rehabilitation of lowland forest in Java, Indonesia - SURYO HARDIWINOTO; FIQRI ARDIANSYAH; Widiyatno Widiyatno (Society for Indonesian Biodiversity, 2021)
Abstract. Hardiwinoto S, Ardiansyah F, Widiyatno. 2021. Application of selected teak clone and organic fertilizer to accelerate rehabilitation of lowland forest of Java, Indonesia. Biodiversitas 22: 1750-1756. Lowland forest in Java Island Indonesia is dominated by teak forest. However, for some decades, the forest has degraded and decreased teak wood production. Rehabilitation of the degraded forest is needed to accelerate the forest land cover. Vegetative propagation of selected clones is one of the techniques used in the asexual reproduction of plants to maintain superior genetics from ancestors to their offspring. In addition, adding organic fertilizer can improve the chemical and physical properties of degraded sites. In this study, vegetative propagation techniques of selected teak clones and addition of organic fertilizer were used to rehabilitate the degraded forest. The objectives of the research were to determine the best propagation technique and appropriate dosage of organic fertilizer toward the early growth of clonal teak plantations. The results showed that the height and diameter parameters did not significantly differ for vegetative propagation and interaction with organic fertilizer dosage (P > 0.05). However, the dosage of organic fertilizer significantly increased the DBH of the teak (P < 0.05), although the height parameter did not significantly differ among dosages of organic fertilizer (P > 0.05). The best dosage of organic fertilizer was 5 kg/individual, under which the average growth in height and diameter of teak at 14 months was 3.79 and 5.60 cm, respectively. This suggests that vegetative propagation of selected teak clones and addition of 5 kg/individual organic fertilizer could be implemented to support the successful rehabilitation of degraded forests.